If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -10 = y + -7 Reorder the terms: -10 + 2y = y + -7 Reorder the terms: -10 + 2y = -7 + y Solving -10 + 2y = -7 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. -10 + 2y + -1y = -7 + y + -1y Combine like terms: 2y + -1y = 1y -10 + 1y = -7 + y + -1y Combine like terms: y + -1y = 0 -10 + 1y = -7 + 0 -10 + 1y = -7 Add '10' to each side of the equation. -10 + 10 + 1y = -7 + 10 Combine like terms: -10 + 10 = 0 0 + 1y = -7 + 10 1y = -7 + 10 Combine like terms: -7 + 10 = 3 1y = 3 Divide each side by '1'. y = 3 Simplifying y = 3
| 11+11y=-6y-10 | | 2x+568x-10x= | | 2(1+2n)=-(-7-4n)-1 | | 2(1+2n)=-(-7-4r)-1 | | -15w+13=-193 | | 14.75+1x=5p | | 31-10x=16+5x | | -2(n+2)=-2(3n-6) | | 6=2r-5r | | 9x-4x+124=9x+48 | | 6-8x=6x-10x-18 | | 20w(7.50h)-p=6.75 | | 2(4-2x)-8=-4 | | -2(m-8)+14m=88 | | 11+11y=6y-10 | | 6(1-4n)+3(5n+7)=1-5n-2 | | 6(1-4v)+3(5n+7)=1-5n-2 | | R=4x+14 | | 7n=-3n+6n | | 3x+22x-1=5(5x+8) | | (x-4)+2x=0 | | 2x+6=2x-36 | | -10y=3y-13 | | 16x-3x=-26 | | 10-7c=32 | | (2x-5)3-8x=11x | | 60+20s=175+15s | | 0.75b+10.50=13.50 | | 7n-3(m+4)=-6n-12 | | 6x+8y=20 | | 9v=-108 | | 4n+11=-7 |